1999
DOI: 10.1093/humrep/14.9.2386
|View full text |Cite
|
Sign up to set email alerts
|

Pre-implantation endometrial leukocytes in women with recurrent miscarriage

Abstract: Immunohistochemistry was used to investigate the leukocyte populations in the endometrium of women suffering recurrent miscarriage. Mid-luteal phase endometrial biopsies were taken from 22 patients with idiopathic recurrent miscarriage and from nine women with normal obstetric histories. The samples were dated histologically and stained with a panel of monoclonal antibodies to identify leukocytes. The outcome of any pregnancy in subsequent cycles following the biopsy was determined. Similar numbers of cluster … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

7
178
1
6

Year Published

2001
2001
2021
2021

Publication Types

Select...
5
1
1

Relationship

0
7

Authors

Journals

citations
Cited by 269 publications
(194 citation statements)
references
References 21 publications
7
178
1
6
Order By: Relevance
“…All studies of decidua in miscarriage suffer from the criticism of 'cause or result' since samples are collected after clinical presentation and any alteration in leukocyte populations may simply reflect an inflammatory response to pregnancy demise. Nevertheless, macrophage numbers were also increased in luteal phase endometrium from women with a history of recurrent miscarriage, supporting a causative rather than a secondary effect (Quenby et al, 1999).…”
Section: Macrophages In Pathological Pregnancymentioning
confidence: 86%
See 3 more Smart Citations
“…All studies of decidua in miscarriage suffer from the criticism of 'cause or result' since samples are collected after clinical presentation and any alteration in leukocyte populations may simply reflect an inflammatory response to pregnancy demise. Nevertheless, macrophage numbers were also increased in luteal phase endometrium from women with a history of recurrent miscarriage, supporting a causative rather than a secondary effect (Quenby et al, 1999).…”
Section: Macrophages In Pathological Pregnancymentioning
confidence: 86%
“…For example, increased numbers of CD56+ NK cells have been reported in decidua of women with sporadic miscarriage compared with controls (Zenclussen et al, 2001), although we were not able to confirm this finding in a study of placental bed biopsies from aneuploid and euploid miscarriages from 8 -20 weeks gestation, compared with normal pregnancy (Scaife et al, 2004). Despite the inconsistency of data for decidual and peripheral blood leukocytes, there are several independent reports from different groups of increased numbers of uNK cells, detected using immunohistochemistry, in luteal phase endometrium of both women with unexplained recurrent miscarriage and recurrent implantation failure (Quenby et al, 1999;Clifford et al, 1999;Laird et al, 2005;Tuckerman et al, 2007). Furthermore, it has been suggested that high uNK cell numbers in mid-secretory phase endometrium from women with recurrent miscarriage predicted miscarriage in subsequent pregnancy (Quenby et al, 1999).…”
Section: Uterine Nk Cells In Pathological Pregnancymentioning
confidence: 99%
See 2 more Smart Citations
“…Idiopathic recurrent miscarriage has traditionally been associated with alloimmune factors, in which uterine CD56+/16 NK cells have been implicated (Quenby et al, 1999). In vitro studies suggest that pregnancy may result in uterine T-cell activation along the Th-2 pathway, resulting in blocking antibodies which mask trophoblast antigens (Wegmann et al, 1993).…”
Section: Immunotherapymentioning
confidence: 99%